Penerapan Strategi Promotion Mix Pada Kedai Kopi Santaria - Ivian Dorryn (ConCEPt - Conference on Community Engagement Project, 2021)
In the preparation of drafting this practical work activity report aims to assist the promotion process at Santaria restaurants in attracting the attention of the general public and strengthening branding to increase sales of Santaria restaurants. In the application of this promotional mix using interview, observation, and survey methods. The implementation implemented is a promotional mix design in the form of advertising in the form of distributing brochures and printing food menus in the form of stickers and books, digital marketing in the form of creating a Facebook account which is made with the aim of being better known by the wider Batam community. Implementation results designed for restaurants are paying off by increasing customers and sales. In this study indicates that the application of the promotional mix designed by the author can be applied properly by the Santaria restaurant.